Pengaruh Lifestyle, Word Of Mouth Dan Brand Image Terhadap Keputusan Pembelian Handbody Scarlett (Studi Kasus Pada Masyarakat Lingkungan XI Jl. Garu III Medan Amplas) - Ramadani, Putri; Rukmini; Safina, Wan Dian; Rahmat, Muhammad (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Many factors influence consumer decisions regarding Handbody Scarlett (Case Study, Environment XI Jl. Garu III, Amplas Community, Medan), including lifestyle, word of mouth marketing, and brand photography. This research aims to understand consumer welfare, word of mouth marketing and determine the image of Handbody Scarlett (Case Study of the Amplas Medan XI Community Circle Jl. Garu III). The research method used in this research is multivariate research, and the sampling method in this research is the Slovin sample, the population is 190 people, so the sample size is 85 participants. The data collection methods used are observation and surveys. The data analysis process used is multi-row iterative. The research results show that lifestyle changes have a partial effect on consumer decision making. Topic change messages influence consumer purchasing decisions. Changes in image patterns influence consumer purchasing decisions. Meanwhile, lifestyle changes, word-of-mouth marketing and brand image influence consumer decisions regarding Handbody Scarlett (Case Study of the Median Amplas XI Community Circle Jl. Garu III).